A large-scale application of project prioritization to threatened species investment by a government agency - Brazill-Boast, J; Williams, M; Rickwood, B; Partridge, T; Bywater, G; Cumbo, B; Shannon, I; Probert, W; Ravallion, J; Possingham, H; Maloney, R (Public Library of Science, 2018)
In a global environment of increasing species extinctions and decreasing availability of funds with which to combat the causes of biodiversity loss, maximising the efficiency of conservation efforts is crucial. The only way to ensure maximum return on conservation investment is to incorporate the cost, benefit and likelihood of success of conservation actions into decision-making in a systematic and objective way. Here we report on the application of a Project Prioritization Protocol (PPP), first implemented by the New Zealand Government, to target and prioritize investment in threatened species in New South Wales, Australia, under the state's new Saving our Species program. Detailed management prescriptions for 368 threatened species were developed via an expert elicitation process, and were then prioritized using quantitative data on benefit, likelihood of success and implementation cost, and a simple cost-efficiency equation. We discuss the outcomes that have been realized even in the early stages of the program; including the efficient development of planning resources made available to all potential threatened species investors and the demonstration of a transparent and objective approach to threatened species management that will significantly increase the probability of meeting an objective to secure the greatest number of threatened species from extinction.